In Vitro Generation of Brain Regulatory T Cells by Co-culturing With Astrocytes - Yamamoto, Shinichi; Matsui, Ako; Ohyagi, Masaki; Kikutake, Chie; Harada, Yoshihiro; Iizuka-Koga, Mana; Suyama, Mikita; Yoshimura, Akihiko; Ito, Minako (Frontiers in Immunology, 2022)
Regulatory T cells (Tregs) are normally born in the thymus and activated in secondary lymphoid tissues to suppress immune responses in the lymph node and at sites of inflammation. Tregs are also resident in various tissues or accumulate in damaged tissues, which are now called tissue Tregs, and contribute to homeostasis and tissue repair by interacting with non-immune cells. We have shown that Tregs accumulate in the brain during the chronic phase in a mouse cerebral infarction model, and these Tregs acquire the characteristic properties of brain Tregs and contribute to the recovery of neurological damage by interacting with astrocytes. However, the mechanism of tissue Treg development is not fully understood. We developed a culture method that confers brain Treg characteristics in vitro. Naive Tregs from the spleen were activated and efficiently amplified by T-cell receptor (TCR) stimulation in the presence of primary astrocytes. Furthermore, adding IL-33 and serotonin could confer part of the properties of brain Tregs, such as ST2, peroxisome proliferator-activated receptor γ (PPARγ), and serotonin receptor 7 (Htr7) expression. Transcriptome analysis revealed that in vitro generated brain Treg-like Tregs (induced brain Tregs; iB-Tregs) showed similar gene expression patterns as those in in vivo brain Tregs, although they were not identical. Furthermore, in Parkinson’s disease models, in which T cells have been shown to be involved in disease progression, iB-Tregs infiltrated into the brain more readily and ameliorated pathological symptoms more effectively than splenic Tregs. These data indicate that iB-Tregs contribute to our understanding of brain Treg development and could also be therapeutic for inflammatory brain diseases.